Burkitt’s lymphoma presenting as mandibular swelling – report of a case and - S. H. C. Tsui,* M. H. Wong, W. Y. Lam (Blackwell Synergy, 2000)
Patients with acute swelling in or around the jaws often present to dental or oral surgeons. In most cases, the cause is acute infection of odontogenic origin and appropriate treatment given. In rare cases, the diagnosis is not obvious and the differential diagnosis of a malignancy may be missed if one does not suspect it and if there are no other clinical clues such as loss of weight or neurological deficits. This is particularly so in previously healthy young children.